The Effect of The Loaded Language and The Appearance of Sadism In Kurdish Society - Tara Mushir Salih; Omed Barzan Brzo (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Language levers, which refer to all kinds of harsh language, threats, insults, and insults, contain the meanings of severity and cruelty in Arabic. In the amount of harsh language or harsh language, harsh language can be used to convey unpleasant and violent thoughts and feelings by allowing the audience to understand,the meaning of the word or statement. the "linguistic burden" is physical by default,and can extend to the oral area of speech and writing in such a way as to produce physical effects, that is, through oral language or severe physical torture to the extent that sexual desires are satisfactory in this way. This study is entitled " The effect of the Loaded language and the appearance of sadism in Kurdish society". The research is based on two sections: introduction, content, results, and sources, in addition to the summary of the research written in Arabic and English. The first part, entitled "The psychology of stressful language", includes the following topics: the concept and definition of cumbersome language, cumbersome language such as psychological reaction. The second part is entitled " The effect of the Loaded language and the appearance of sadism in Kurdish society ", and includes: Sadism, Parts of Sadism: -1- Improper stimulation, mental or sexual stimulation, 2- Sincere - Sexual attraction of Maga, 3- Sadism or compensation, Sadism and Chadnifrod, the concept of everyday sadism, sexual sadism, manifestations of sadistic behavior, sadism and the emotional process, dissonance of the sadistic personality.